Evaluating multimodal literacy: Academic and professional interactions around student-produced instructional video tutorials. (April 2022) - Dressen-Hammouda, Dacia; Wigham, Ciara R.
Abstract: This paper offers a reflection on how academic and professional interactions can help guide best practices for constructing viable evaluation grids to assess multimodal literacy. Preparing English-language learners for today's digitally and culturally complex workplace environment is a central concern in English as a second language (L2) teaching environments. It requires meeting specific teaching goals, such as supporting traditional print and multimodal literacies as well as increasing learners' English-language fluency and appropriateness. Our study focuses on an underexplored professional multimodal genre – instructional video tutorials – and proposes a multimodal evaluation grid incorporating theoretical concepts and empirical results from multimodal linguistics and multimedia learning. We examine how four video communication professionals use the grid to measure the effectiveness of students' video tutorials and identify areas for improvement. We present results for three areas for which the experts considered students did not meet expected professional standards: information organization, timing, and L2 spoken language narration. Our findings suggest possibilities for introducing appropriate forms of action or intervention into teaching multimodal design projects to better prepare L2 English students to meet workplace multimodal literacy requirements.